Synchronous Occurrence of Collagenous and Pseudomembranous Colitis - Z Vesoulis; G Lozanski; T Loiudice (Canadian Journal of Gastroenterology)
Synchronous collagenous and pseudomembranous colitis has not been previously reported. A 73-year-old woman presented with chronic watery diarrhea and abdominal cramping of six weeks’ duration. Biopsies of the colon revealed findings of collagenous colitis involving the endoscopically normal right colon, and superimposed collagenous and pseudomembranous colitis involving the rectosigmoid colon. Endoscopically, the left colon revealed discrete ulcerative plaques, and Clostridium difficile toxin A assay was positive. The patient partially responded to a three-week regimen of metronidazole, and symptoms resolved completely with subsequent steroid therapy. At follow-up endoscopy four months later, colon biopsies demonstrated persistence of subepithelial collagen but no pseudomembranes. The patient remained asymptomatic during this interval. Collagenous colitis has been reported in association with other inflammatory bowel diseases, including lymphocytic colitis, sprue and idiopathic inflammatory bowel disease. This unique association of collagenous colitis with an endotoxigenic inflammatory bowel disease is presented with a review of related disease features.